Genesis of the Mianhuakeng uranium deposit, South China: Constraints from in-situ sulfur isotopes and trace elements of pyrite. (May 2022) - Zhang, Yiyang; Zhong, Fujun; Liu, Jungang; Qi, Jiaming; Pan, Jiayong; Xia, Fei; Li, Haidong
Abstract: The Mianhuakeng U deposit is the largest granite-type deposit in South China, ore bodies commonly occur in fault zones of Youdong and Changjiang geanites. However, the genesis and mineralization processes remain poorly understood. The main metal sulfide in this deposit is pyrite, which can be classified into four stages based on its mineral assemblages and textures: pre-ore stage (Py Ⅰ), early-syn-ore stage (Py Ⅱa), syn-ore stage (Py Ⅱb), and post-ore stage (Py Ⅲ). In this study, we present in-situ sulfur isotopic and trace element compositions of different stages of pyrite, obtained using laser ablation multi-collector inductively coupled plasma mass spectrometry (LA-(MC)-ICP-MS), to reveal the evolution of the ore-forming fluid and ore genesis. The δ 34 S values of pyrite ranged from −18.5‰ to −6.8‰, with peaks at −8‰ to −10‰, similar to the δ 34 S values of the host rock. The large range variations in δ 34 S values result from the mixing of ore-forming fluid and meteoric water. The U and W contents of all pyrite showed a strong positive linear relationship with their concentrations, indicating that the host granites were likely the main source of metal for U mineralization. From the pre-ore to the syn-ore stage, the contents of Co and Ni decreased, and those of Cu and As increased, while Ni/Se ratios decreased, suggesting that the temperature and oxygen fugacity of the ore-forming fluids decreased. There are significant vertical variations in δ 34 S values and trace element compositions of pyrite in the ore body of the Mianhuakeng deposit. From the bottom to the top, the oxygen fugacity and temperature of the ore-forming fluids increased and decreased, respectively. These results, combined with published data, suggest that the initial hydrothermal fluids likely originated from meteoric water and mixed with mantle-derived CO2 circulating within host granites and leached U and other metals (e.g., W) to form ore-forming fluids. As the temperature, oxygen fugacity, and pressure decreased, the hydrothermal solution outgassed and released CO2 while U 6+ was reduced to U 4+ and precipitated as pitchblende, resulting in U mineralization. Thus, the combined effect of temperature, pressure, and oxygen fugacity controlled U mineralization in the Mianhuakeng deposit. In particular, change in oxygen fugacity acted as an important factor affecting uranium mineralization. Highlights: Host granites are the main source of U mineralization. Temperature and oxygen fugacity of ore-forming fluids decreased through ore stages. Fluids mixing produced vertical mineralization zoning. Oxygen fugacity decreased is an important factor affecting uranium mineralization.